2020
DOI: 10.3390/cancers12082193
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Modulating Effects of Conventional Therapies in Colorectal Cancer

Abstract: Biological heterogeneity and low inherent immunogenicity are two features that greatly impact therapeutic management and outcome in colorectal cancer. Despite high local control rates, systemic tumor dissemination remains the main cause of treatment failure and stresses the need for new developments in combined-modality approaches. While the role of adaptive immune responses in a small subgroup of colorectal tumors with inherent immunogenicity is indisputable, the challenge remains in identifying the optimal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…The pro‐immunogenic role lies in its ability to promote T cell priming by inducing tumor‐associated antigens, upregulating major histocompatibility complex class‐I (MHC‐I) expression and generating an in situ vaccine [ 12 , 13 , 14 ]. In contrast, immune suppressive cells and molecules such as regulatory T cells (Tregs), myeloid‐derived suppressor cells (MDSCs), tumor‐associated macrophages (TAMs), and transforming growth factor β (TGF‐β) are stimulated by irradiation (IR) [ 15 , 16 , 17 , 18 ]. In addition, accumulating evidence demonstrates that IR‐induced cytoplasmic DNA could activate the cyclic GMP‐AMP synthase (cGAS)‐stimulator of interferon genes (STING) pathway, promoting interferon signaling and dendritic cell (DC) activation, which links DNA damage to innate immune activation and the adaptive antitumor response [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pro‐immunogenic role lies in its ability to promote T cell priming by inducing tumor‐associated antigens, upregulating major histocompatibility complex class‐I (MHC‐I) expression and generating an in situ vaccine [ 12 , 13 , 14 ]. In contrast, immune suppressive cells and molecules such as regulatory T cells (Tregs), myeloid‐derived suppressor cells (MDSCs), tumor‐associated macrophages (TAMs), and transforming growth factor β (TGF‐β) are stimulated by irradiation (IR) [ 15 , 16 , 17 , 18 ]. In addition, accumulating evidence demonstrates that IR‐induced cytoplasmic DNA could activate the cyclic GMP‐AMP synthase (cGAS)‐stimulator of interferon genes (STING) pathway, promoting interferon signaling and dendritic cell (DC) activation, which links DNA damage to innate immune activation and the adaptive antitumor response [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 68 The high TMB in these tumors has been correlated to their infiltration with neoantigen-specific T cells 69 and their response to chemotherapy 70 or immune checkpoint immunotherapy 71 , 72 : both therapies with immune-stimulating capacity. 73 , 74 Although pMMR-MSS tumors are generally considered TMB low, it has been shown that stratification of patients according to TMB predicts their overall survival following chemotherapy plus cetuximab (anti-epidermal growth factor receptor mAb) or bevacizumab (anti-vascular endothelial growth factor mAb). 68 For these tumors, the TMB can be considered a proxy for the presence of neoantigens and T cell abundance in the tumor.…”
Section: Neoantigens In Crc Immunotherapymentioning
confidence: 99%
“…According to one study, increased circulating fms-related tyrosine kinase 3 ligand (FLT3LG) caused by neoadjuvant cytotoxic treatment in rectal cancer patients activated the anti-tumor immune response. Functionally active adaptive immune cells may eliminate microscopic tumor cells, lowering the risk of tumor metastasis [ 136 ]. The combination of IL-12 gene therapy and chemotherapy has shown the ability to transform the metastatic microenvironment into a more immunogenic phenotype by reducing Treg, MDSC, and M2 macrophages [ 132 ].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%